2013
DOI: 10.5588/pha.13.0083
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and treatment outcomes in Palestine refugees in UNRWA primary health care clinics in Jordan

Abstract: decision was made to improve the practice and recording of routine clinic measurements and to expand the use of cohort analysis to other PHC clinics that already had e-Health.The aim of the present study was to use the principle of cohort analysis to report on the burden of DM and treatment outcomes of patients with DM registered at six PHC clinics in Jordan. Specific objectives were to report on 1) the number and characteristics of new patients with DM registered in the second quarter (Q2) of 2013 and of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 16 publications
0
80
1
4
Order By: Relevance
“…Only 55.5% of cases with co-existing hypertension had their last recorded BP ≤ 140/90 mm Hg and only 28.2% had their BP ≤ 130/80 mm Hg. Hypertension control rates in this study are lower compared to the cumulative cohort data from six clinics in Jordan that use the E health record system where 87% of all patients had BP ≤ 140/90 mm Hg [7]. Uncontrolled hypertension in the setting of relatively poor glucose control is fertile ground for macro and microvascular complications particularly myocardial infarction, stroke, nephropathy and retinopathy.…”
Section: Discussioncontrasting
confidence: 56%
“…Only 55.5% of cases with co-existing hypertension had their last recorded BP ≤ 140/90 mm Hg and only 28.2% had their BP ≤ 130/80 mm Hg. Hypertension control rates in this study are lower compared to the cumulative cohort data from six clinics in Jordan that use the E health record system where 87% of all patients had BP ≤ 140/90 mm Hg [7]. Uncontrolled hypertension in the setting of relatively poor glucose control is fertile ground for macro and microvascular complications particularly myocardial infarction, stroke, nephropathy and retinopathy.…”
Section: Discussioncontrasting
confidence: 56%
“…All studies were published between 1992 and 2018, with thirty-three published since 2011. Thirty-eight studies reported on populations affected by armed conflict, [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33]35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] two reported on populations affected by natural disasters, 34,37 and one on all crisis types. 26 Thirty-four studies were conducted in the protracted crisis phase (crisis duration greater than six months), [17][18][19][20][21][22][23][24][25]…”
Section: Existing Evidencementioning
confidence: 99%
“…Khader and colleagues highlighted the role played by e-Health in supporting drug-procurement policies, monitoring NCD risk factors, and evaluating the quality of care over time by identifying the occurrence of late complications of NCDs (25)(26)(27)(28)(29). Additionally, the Agency's internal assessments reported widespread satisfaction with the new FHT approach among both providers and patients.…”
Section: Conclusion and Way Forwardmentioning
confidence: 99%
“…When any family member attends a health centre, the record highlights non-attendance by other members. UNRWA evaluations show that e-Health provides accurate information about numbers of patients, services provided and outcomes of care (25)(26)(27)(28)(29).…”
Section: Clinical Information Systemsmentioning
confidence: 99%
See 1 more Smart Citation